The dilution of peri-urban socio-cultural identity: an insight into policies and strategies in Malaysia and the European Commission - Mazlan, Maizura; Ismail, Nor Atiah; Mohd Yusof, Mohd Johari; Abdul Aziz, Faziawati (Springer Nature, 2022)
The peri-urban area or zones happen all over the globe as urban areas are rapidly expanding, and over the coming decades, the urbanization process will continue to grow exponentially. The peri-urban area, naturally being transitional and ambiguity in its character has put this area in obscurity. The dynamic changes in the social and cultural aspect will reflect the peri-urban area identity. Being neither urban nor completely rural, peri-urban areas show the common characteristic of equivocalness, despite their diversity in terms of definition, formation, and measure. In contrast with the concept that urban and rural areas were defined by very definite land-use patterns and unambiguous socio-cultural, the implicit boundaries between this locations and peri-urban area were unclearly defined. Thus, this article seeks to attain the objectives: (i) examining the peri-urban definitions, policy, and strategies implemented by Malaysia and Europe; and (ii) to highlight the importance of establishing more appropriate strategies for this particular area. This qualitative study, with content analysis, provides a comprehensive review on reviving the socio-cultural identity of the dynamic peri-urban. The finding shows that with good and appropriate planning, as well as strategies, can benefit the peri-urban sustainability. These features and their interactions have made them recognized as large peri-urban regions or interfaces to become a critical in their own research area. On account of the unique identity and the connection between these peri-urban areas and metropolitan cities has been recognized by their own right as essential areas or interfaces (PUI). The contribution of this paper is to alert the local government, especially the policymaker on the importance of the peri-urban socio-cultural identity in controlling the encroachment of development.